Future direction of Au agromining on how to solve artisanal and small scale gold mining problems - Abd Mujahid Hamdan; Rizna Rahmi; Abd Hafidz; R Risplaman (Journal of Degraded and Mining Lands Management, 2021)
Indonesia is one of the countries with the largest Au deposited. Gold mining has been the backbone of Indonesia’s economy. However, Indonesia also faces huge problems of Artisanal and Small Scale Gold Mining (ASGM) in a number of areas of Indonesia. A number of problems follow this Au mining method, including environmental, social and economic problems. Green innovation and technologies are needed to solve the problems. To date, Au agromining has been considered as a technology that can solve the numerical problems of Au conventional mining in the sector mentioned before. Gold agromining also has been proposed as a solution for the ASGM problem in Indonesia. However, until now, there have been no reports on the use of Au agromining technology in Indonesia. In fact, agromining research has been very advanced and is considered very prospective. This paper outlines the potentials of Au agromining to be implemented in Indonesia to overcome the social and environmental problems of ASGM.